PENGARUH MODEL TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA FLIPCHART TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SD NEGERI 2 KARANG SARI - Dinda Sri Athiya Lilla; Sowiyah; Jody Setya Hermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of this research is the low mathematics learning outcomes of students, and educators have not implemented the Team games tournament (TGT) model. The purpose of this study was to determine the effect of the Team games tournament (TGT) model assisted by flipchart media on mathematics learning outcomes of grade IV of Elementary School 2 Karang Sari. This type of research uses quantitative research with a quasi-experimental method and a research design using a pretest posttest control group design. The research sample was students in grade IV of Elementary School 2 Karang Sari with a total of 19 students. The research sampling technique used a purposive sampling technique. The data analysis technique used a simple linear regression test, obtained F count of 1998.329> Ftable 4.45 with a significant value of 0.000 < 0.05. The results of the study are that there is an influence of the Team games tournament (TGT) model assisted by flipchart media on the learning outcomes of mathematics in grade IV of SD Negeri 2 Karang Sari.